2007
DOI: 10.1902/jop.2007.060269
|View full text |Cite
|
Sign up to set email alerts
|

The Long‐Term Effect of a Mouthrinse Containing Essential Oils on Dental Plaque and Gingivitis: A Systematic Review

Abstract: When used as an adjunct to unsupervised oral hygiene, EO provides an additional benefit with regard to plaque and gingivitis reduction as compared to a placebo or control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
129
0
14

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(159 citation statements)
references
References 41 publications
(78 reference statements)
11
129
0
14
Order By: Relevance
“…15,16 It is possible to generalize this evidence indirectly from clinical trials with subjects not using fixed appliances to those using them. However, it is very important that welldesigned clinical trials be conducted to provide evidence regarding the efficacy of oral antiseptics in reducing plaque and gingivitis in orthodontic patients.…”
Section: Final Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 It is possible to generalize this evidence indirectly from clinical trials with subjects not using fixed appliances to those using them. However, it is very important that welldesigned clinical trials be conducted to provide evidence regarding the efficacy of oral antiseptics in reducing plaque and gingivitis in orthodontic patients.…”
Section: Final Considerationsmentioning
confidence: 99%
“…13,14 Several clinical trials have been conducted in order to test the efficacy and safety of these products. Systematic reviews of these clinical trials have demonstrated the efficacy of mouthwashes containing chlorhexidine gluconate, 15 essential oils 15,16 and cetylpyridinium chloride. 17 A recent review of systematic reviews compared these three active principles, showing that mouthwashes containing chlorhexidine present higher anti-plaque and anti-gingivitis efficacy (mean reduction of 40% and 28%, respectively) followed by essential oils (mean reduction of 27% and 18%, respectively) and cetylpyridinium chloride (mean reduction of 15% and 13%, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…8,74 EO has also been proven to provide significant effects against plaque and gingivitis. 36,80 Under specific clinical conditions, EO showed comparable results to those of CHX. 81 One important aspect that certainly contributes to this superiority is their ability to penetrate biofilms.…”
Section: Effectiveness and Expected Benefits Of Mouthrinsesmentioning
confidence: 80%
“…71 Moreover, its long-term use is also supported by the lack of adverse events. In a systematic review published by Stoeken et al 36 it was demonstrated that most studies agreed that EO did not produce more tooth-staining than the control products. Some manufacturers indicate CPC long-term use; however, published articles failed to support this indication.…”
Section: How To Use and When To Indicate Mouthrinsesmentioning
confidence: 98%
See 1 more Smart Citation